Striving for success or addiction? Exercise dependence among elite Australian athletes - McNamara, J.; McCabe, M. P. (Journal of Sports Sciences, 2012)
Exercise dependence is a condition that involves a preoccupation and involvement with training and exercise, and has serious health and performance consequences for athletes. We examined the validity of a biopsychosocial model to explain the development and maintenance of exercise dependence among elite Australian athletes. Participants were 234 elite Australian athletes recruited from institutes and academies of sport. Thirty-four percent of elite athletes were classified as having exercise dependence based on high scores on the measure of exercise dependence. These athletes had a higher body mass index, and more extreme and maladaptive exercise beliefs compared to non-dependent athletes. They also reported higher pressure from coaches and teammates, and lower social support, compared to athletes who were not exercise dependent. These results support the utility of a biopsychosocial model of exercise dependence in understanding the aetiology of exercise dependence among elite athletes. Limitations of the study and future research directions are highlighted.